Annual Editor Report - Barth, Mary E. (The Accounting Review, 2019)
editorial| August 12 2020 Annual Editor Report Mary E. Barth Mary E. Barth Stanford University Search for other works by this author on: This Site PubMed Google Scholar The Accounting Review (2019) 94 (6): 1a–21. https://doi.org/10.2308/accr-10749 Views Icon Views Article contents Figures & tables Video Audio Supplementary Data Share Icon Share Facebook Twitter LinkedIn Email Tools Icon Tools Get Permissions Cite Icon Cite Search Site Citation Mary E. Barth; Annual Editor Report. The Accounting Review 1 November 2019; 94 (6): 1a–21. doi: https://doi.org/10.2308/accr-10749 Download citation file: Ris (Zotero) Reference Manager EasyBib Bookends Mendeley Papers EndNote RefWorks BibTex toolbar search Search nav search search input Search input auto suggest Search This content is only available as a PDF. Article PDF first page preview Close Modal You do not currently have access to this content.